Physiological and Biochemical Adaptations to High Altitude in Tibetan Frogs, Nanorana parkeri - Niu, Yonggang; Zhang, Xuejing; Xu, Tisen; Li, Xiangyong; Zhang, Haiying; Wu, Anran; Storey, Kenneth B.; Chen, Qiang (Frontiers in Physiology, 2022)
The Xizang plateau frog, Nanorana parkeri (Anura: Dicroglossidae), is endemic to the Tibetan Plateau, ranging from 2850 to 5100 m above sea level. The present study explores physiological and biochemical adaptations to high altitude in this species with a particular emphasis on parameters of hematology, oxidative stress, and antioxidant defense in adult and juvenile N. parkeri collected from high (4600 m a.s.l) and low (3400 m a.s.l) altitudes. Hematological results showed that hemoglobin concentration ([Hb]), hematocrit (Hct), and red blood cell (RBC) counts were significantly higher in high-altitude N. parkeri. High-altitude juveniles had lower RBC sizes than low-altitude juveniles. Higher levels of GSH and GSSG were indicated only in juveniles from high altitude, not in adults. High-altitude individuals also showed lower oxidative damage, assessed as malondialdehyde (MDA) and carbonyl groups (CG) in the liver. High-altitude adults also showed higher activities of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), and glutathione-S-transferase (GST) as well as total antioxidant capacity (T-AOC) in the liver as compared to low-altitude adults. Moreover, higher GPX activity and T-AOC were observed in the heart and brain of high-altitude adults. Liver CAT, GPX, and T-AOC showed significant increases in high-altitude juveniles. Vitamin C content was also higher in the heart of high-altitude frogs compared to low-altitude individuals. In summary, the high-altitude population of N. parkeri showed more robust hematological parameters, less oxidative damage, and stronger antioxidant defenses than the low-altitude population, all contributing to increased protection for survival in high-altitude environments.